Low rate of early vertical transmission of HIV supports the feasibility of effective implementation of the national PMTCT guidelines in routine practice of referral hospitals in Cameroon. (3rd July 2019) - Penda, Calixte Ida; Tejiokem, Mathurin Cyrille; Sofeu, Casimir Ledoux; Ndiang, Suzie Tetang; Ateba Ndongo, Francis; Kfutwah, Anfumbom; Guemkam, Georgette; Warszawski, Josiane; Faye, Albert; Study Group, the ANRS-Pediacam
ABSTRACT: Background : Vertical (VT) transmission of HIV remains a public health concern in sub-Saharan Africa. Objective : To investigate the VT rate and factors associated with transmission in routine practice in three referral hospitals in Cameroon. Methods : All HIV-infected mothers who delivered in maternity wards or sought paediatric services during the first postnatal week from November 2007 to October 2010 were invited to participate in the ANRS-Pediacam cohort. Their infants were followed at 6, 10 and 14 weeks of life and HIV status was determined from the 6th week of life using real-time PCR. For those who were breastfed and negative at the first PCR, a second test was performed 6 weeks after breast-feeding was stopped. Logistic regression was performed to identify the independent risk factors of VT. Results : Overall, 2053 HIV-exposed infants were enrolled. Of these, 1827 were tested for HIV including 1777 before the age of 3 months, and 59 were HIV-infected, resulting in an overall early VT rate of 3.3% (CI 2.5–4.3). The VT rate was significantly associated with the type of maternal exposure to ART (0.5%, 2/439, p<0.001, CI 0.0-1.6) in mothers who commenced HAART before pregnancy, 1.9% (6/321, CI 0.7–4.0) in mothers who commenced HAART during pregnancy, 4.1% (34/837, CI 2.8–5.6) in those on short-course ART and 11.1% (17/153, CI 6.6–17.2) in mothers not receiving ART. On multivariate analysis, the type of exposure to ART remained significantly associated with being small for gestational age (aOR 5.0, CI 2.4–10.3, p < 0.001) and female gender (aOR 2.1, CI 1.2–3.8, p = 0.01). Conclusion : The successfully low rate of VT transmission of HIV in mothers who commenced HAART in early pregnancy strongly supports the need to improve access to diagnosis and early treatment of all women of childbearing age with HIV through the national PMTCT programme. Abbreviations : ANRS: French National Agency for Research on AIDS and Viral Hepatitis; ART: antiretroviral therapy; ARV: antiretroviral; AUDIPOG: Association des Utilisateurs de Dossiers Informatisés en Pédiatrie, Obstétrique et Gynécologie; CHM/MCC-CBF: The Central Hospital Maternity/Mother and Child Centre of the Chantal Biya Foundation; EHC: Essos Hospital Centre; EPI: Expanded Programme on Immunization; HAART: highly active antiretroviral therapy; HBV: hepatitis B virus; IQR: interquartile range; LH: Laquintinie Hospital; MTCT: mother-to-child transmission; NVP: nevirapine; Pediacam: Pediatrie Cameroun; PMTCT: prevention of mother-to-child transmission; SGAG: small for gestational age and gender; UNAIDS: Joint United Nations Program on HIV/AIDS; WHO: World Health Organization; ZDV: zidovudine; 3TC: lamivudine.